Discrete element method (DEM) modelling of rock flow and breakage within a cone crusher - Li, Huiqi (2013)
A cone crusher is a crushing machine which is widely used in the mining, construction and recycling industries. Previous research studies have proposed empirical mathematical models to simulate the operational performance of a cone crusher. These models attempt to match the size distributions of the feed and product streams. The flow of the rock and its breakage within the cone crusher chamber are not explicitly modelled by these methods. Moreover, the ability to investigate the changes in crusher performance affected by changes to the crusher design geometry and/or operating variables (including cavity profile, closed size setting and eccentric speed) are not easily achieved. Improvements to system design and performance are normally achieved by the combination of iterative modifications made to the design and manufacture of a series of prototype machines, and from a subsequent analysis of the results obtained from expensive and time consuming rock testing programs. The discrete element method (DEM) has in recent years proved to be a powerful tool in the execution of fundamental research to investigate the behaviour of granular material flow and rock breakage. Consequently, DEM models may provide the computational means to simulate the flow and breakage of rock as it passes through a cone crusher chamber. Thus, the development of field validated models may provide a cost effective tool to predict the changes in crusher performance that may be produced by incremental changes made to the dimensions or power delivered to the crusher chamber. To obtain an improved understanding of the fundamental mechanisms that take place within a cone crusher chamber, the two processes of rock flow and rock breakage may be decoupled. Consequently, this study firstly characterised the flow behaviour of broken rock through a static crusher chamber by conducting a series of experiments to investigate the flow of regular river pebbles down an inclined chute. A parallel computational study constructed and solved a series of DEM models to replicate the results of these experimental studies. An analysis of the results of these studies concluded that an accurate model replication of the shape of the pebbles and the method used to load the pebbles into the inclined chute were important to ensure that the DEM models successfully reproduced the observed particle flow behaviour. These studies also established relationships between the chute geometry and the time taken for the loaded pebble streams to clear the chute. To investigate the rock breakage behaviour observed within a cone crusher chamber, thirty quasi-spherical particles of Glensanda ballast aggregate were diametrically crushed in the laboratory using a Zwick crushing machine. The crushed rock particles used were of three sieve size fractions: 14-28mm, 30-37.5mm and 40-60mm. The effects that either a variation in the particle size or strength has on and the number and size distribution of the progeny rock fragments produced on breakage were studied. Subsequently, a series of DEM simulation models were constructed and solved to replicate the experimental results obtained from these crushing tests. The aggregate particles were represented by agglomerates consisting of a number of smaller diameter bonded micro-spheres. A new method was proposed to generate a dense, isotropic agglomerate with negligible initial overlap between the micro-spheres by inserting particles to fill the voids in the agglomerate. In addition, the effects that a variation in the particle packing configurations had on the simulated strength and breakage patterns experienced by the model agglomerate rock particles were investigated. The results from these DEM model studies were validated against the experimental data obtained from the ballast rock breakage tests. A comparative analysis of the experimental and modelling studies concluded that once the bond strengths between the constituent micro-spheres matched the values determined from the rock breakage tests, then the numerical models were able to replicate the measured variations in the aggregate particle strengths. Finally, the individual validated DEM aggregate particle flow and breakage modes were combined to construct a preliminary coupled prototype DErvl model to simulate the flow and breakage of an aggregate feed through a cone crusher chamber. The author employed two modelling approaches: the population balance model (PBM) and bonded particle model (BPM) to simulate the observed particle breakage characteristics. The application of the PBM model was successfully validated against historical experimental data available in the literature. However, the potential wider use of the BPM model was deemed impractical due to the high computation time. From a comparative analysis of the particle size distributions of the feed and computed product streams by the two modelling approaches, it is concluded that the simpler PBM produces more practical computationally efficient numerical solutions.